PELAKSANAAN E-TILANG UNTUK MENCEGAH PRAKTIK PUNGUTAN LIAR DI DAERAH SANGATTA - ONY ROSIFANY; VIKTOR HASIHOLAN HUTAGAOL (The Juris, 2021)
The increase in traffic violations is a new challenge for the Police to be able to apply sanctions that are educational but still have a deterrent effect. . "There is a paradigm of instant community thinking in modern times, starting to lose sensitivity in driving, and the lack of driving ethics for orderly, mutual respect, mutual respect, resulting in an increasingly eroded sense of ownership of something. One way to suppress violations is to carry out administrative sanctions ( ticket) by the police. However, what has happened so far is that the ticketing system is often distorted by civilians and unscrupulous members of the police to compromise each other so that their respective interests can be achieved without following the applicable procedures. The type of research used is empirical juridical research, research with field studies to obtain data. The results of the study show that the implementation of E-Tilang is the process of resolving traffic violations cases that have an electronic method so that there are no transactions between traffic violators and law enforcement officers here are traffic police, thus minimizing the opportunity for illegal levies to occur.